Diverse sources of crustal granitic magma:Lu-Hf isotope data on zircon in three Paleoproterozoic leucogranites of southern Finland - Kurhila, Matti; Andersen, Tom; Rämö, O. Tapani (Lithos, 2010)
In this paper we present new LA-MC-ICPMS U-Pb and Lu-Hf isotope data on zircon from three Svecofennian leucogranites of alleged S-type affinity from southern Finland: the Jaani, Perniö and Puruvesi granites. The results show that these granites were emplaced at about 1.86 Ga, 1.84 Ga and 1.79 Ga, respectively. The Jaani and Puruvesi plutons also contain inherited zircon with Paleoproterozoic and Archean ages, whereas zircon from the Perniö pluton has a much more homogeneous (Paleoproterozoic) age distribution. The plutons show significant variation in initial Hf isotope composition: The 1.84 Ga Perniö pluton has a relatively narrow range of initial ε Hf values between - 2 and + 4, the 1.86 Ga Jaani pluton has a much wider range from - 8 to + 8. Igneous zircon of the 1.79 Ga Puruvesi pluton is on average considerably less radiogenic, with all initial ε Hf values below chondritic (- 18 to - 1). The differences in the Hf isotope composition suggest that significantly different (metaigneous to metasedimentary) source rocks contributed to the melts that produced these granites, and thus they should not be considered exclusively S-type granites.